2014
DOI: 10.1371/journal.pone.0112222
|View full text |Cite
|
Sign up to set email alerts
|

Altered Resting-State Amygdala Functional Connectivity after 36 Hours of Total Sleep Deprivation

Abstract: ObjectivesRecent neuroimaging studies have identified a potentially critical role of the amygdala in disrupted emotion neurocircuitry in individuals after total sleep deprivation (TSD). However, connectivity between the amygdala and cerebral cortex due to TSD remains to be elucidated. In this study, we used resting-state functional MRI (fMRI) to investigate the functional connectivity changes of the basolateral amygdala (BLA) and centromedial amygdala (CMA) in the brain after 36 h of TSD.Materials and MethodsF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 49 publications
(68 reference statements)
6
55
1
Order By: Relevance
“…Beyond the increased functional connectivity, we also found decreased functional connectivity between SFA and dACC, consistent with our previous study (Shao et al, ). According to our previous analysis, BL and CM amygdala also showed decreased functional connectivity with dACC, which is closely related to the process of executive control.…”
Section: Discussionsupporting
confidence: 93%
“…Beyond the increased functional connectivity, we also found decreased functional connectivity between SFA and dACC, consistent with our previous study (Shao et al, ). According to our previous analysis, BL and CM amygdala also showed decreased functional connectivity with dACC, which is closely related to the process of executive control.…”
Section: Discussionsupporting
confidence: 93%
“…maternal separation during childhood is linked to upregulation of glucocorticoids, while abuse is linked to downregulation (for a review, please see Lupien et al, ). Future studies could examine whether the relationship between income‐to‐needs and amygdala/precuneus iFC is mediated by (a) the stable presence of the mother or other caregiver, which is thought to attenuate the response of the amygdala to stress by reducing secretion of glucocorticoids from the HPA system (Fareri & Tottenham, )); (b) the same psychosocial variables as explored here but referencing the postnatal, rather than prenatal, time points; (c) sleep deprivation, which is associated with poverty (Patel, Grandner, Xie, Branas, & Gooneratne, ) and also relatively greater amygdala/precuneus iFC (Shao et al, ); or (d) environmental contaminants (Farah, ; Jensen et al, ). Lastly, it should be noted that the framework by Noble and colleagues () was proposed in the context of older children (5–17 years‐of‐age in their study), not 2‐month‐old infants, who may be too young to embody maternal psychosocial stress.…”
Section: Discussionmentioning
confidence: 99%
“…An animal study demonstrated that amygdala played a role in sleep regulation and sleep disturbance may be associated with psychopathology [39], and a recent resting-state functional MRI showed that altered amygdala FC was investigated after 36 h of total sleep deprivation [40]. Therefore, sleep disturbance may involve the functions of amygdala.…”
Section: Discussionmentioning
confidence: 99%